1883 Md. Acts 273-74 - (:unkn) unknown (My University, 1650)
§ 5: Prohibited entering either chamber of legislature with any gun or weapon "upon perill of such fine or censure as the howses shall thinke fitt."
Keywords: SENSITIVE PLACES